Hoping against Hope? On Transformation in Liudmila Petrushevskaia’s Fairy Tales - Zdun, Izabela (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2022)
Jack Zipes mourns the disregard for what he, after Ernst Bloch, refers to as the utopian purpose of the folktale: its capacity for fostering human autonomy and proposing means to alter the world. Building on Bloch’s concept, Zipes contends that what has been missing is seeing life as a process that can be altered and the difficult realities of the present actively faced, not escaped. He asserts that contemporary fairy tales succeed at reviving the utopian function when they are self-reflective and experimental, that is, when they question the forms and themes that the folktale and the fairy tale have developed [Zipes 1983: 170-193]. They succeed also when they nurture the urge for individual and social transformation. This paper examines two fairy tales of a renowned contemporary Russian author Liudmila Petrushevskaia from this perspective. Although veiled in her customary grim vision, which includes existential uncertainty and sociopolitical instability, Petrushevskaia’s fairy tales project an impulse for individual and social change. The paper outlines how the author envisions individual and social transformation in today’s world.